Bacterial Cellulose-Based Materials as Dressings for Wound Healing - Horue, Manuel (2023)
Bacterial cellulose (BC) is produced by several microorganisms as extracellular structures and can be modified by various physicochemical and biological strategies to produce different cellulosic formats. The main advantages of BC for biomedical applications can be summarized thus: easy moldability, purification, and scalability; high biocompatibility; and straightforward tailoring. The presence of a high amount of free hydroxyl residues, linked with water and nanoporous morphology, makes BC polymer an ideal candidate for wound healing. In this frame, acute and chronic wounds, associated with prevalent pathologies, were addressed to find adequate therapeutic strategies. Hence, the main characteristics of different BC structures—such as membranes and films, fibrous and spheroidal, nanocrystals and nanofibers, and different BC blends, as well as recent advances in BC composites with alginate, collagen, chitosan, silk sericin, and some miscellaneous blends—are reported in detail. Moreover, the development of novel antimicrobial BC and drug delivery systems are discussed.